Transient Stability Analysis of a Three-machine Nine Bus Power System Network - Mohd Rizon, Mohamed Juhari; M. A., Salam; Q. M., Rahman (2014)
Transient stability analysis plays an important role for planning, designing and upgrading an existing electrical power system network. In this paper, transient stability analysis is carried out by considering a three-phase fault at the busbars 7 and 4 with the effect of various fault-clearing times. The simulation is carried out using CYME 5.02 power system software with fast decoupled method. It is found that at fault clearing times of 0.05s, 0.1s, and 0.15s, the generators (G2, G3) under test are stable with respect to the simulation time. Whereas, at fault clearing times of 0.2s and 0.3s, these generators are found to be unstable for both faulted busbars 7 and 4. These simulation results are then compared with the proposed model results and are found to be in good agreement. In addition, it has been demonstrated that the transient stability of a system can be improved using control devices.